Identifying Aspects of the Integration of Gus Durs’s Religious Tourism Area with Regionalism Approaches - Jayanata Putra; Dewi Septanti; Murni Rachmawati (IPTEK Journal of Proceedings Series, 2020)
Religious tourism is not separated from the activities which can affect the development of the region and can make it uncontrolled. Developments that can change significantly and uneven can harm various parties around the tourist area. Such developments can lead to a change in function and result in lifestyle shifts surrounding tourist areas. Therefore, integration is necessary for the establishment of a quality tourism plan in urban areas. Integration is an important aspect of changing in urban environments as it can create a space that has the attractiveness and mutual benefit between regions one and the other regions. The research method used is logical argumentation where the research relies on the argument as a reference in the aspects and results of research. Data collection techniques in research with interviews, observations, cognitive mapping and literature studies, after that done with data analysis using legibility analysis to identify the urban form in local and regional, sense of community identity and contributions or its role in the city then proceed with triangulation which aims to check the results of data test or data accuracy, then interpreted according to the context. This study results in what aspects can affect the change in tourist area functions and can be used as an integrated aspect of the surrounding environment.